Stabilization of Pd3−xIn1+x Polymorphs with Pd‐like Crystal Structure and their Superior Performance as Catalysts for Semi‐Hydrogenation of Alkynes. Issue 12 (20th May 2019) - Johnston, Shaun K.; Bryant, Thomas A.; Strong, Jonathan; Lazzarini, Laura; Ibhadon, Alex O.; Francesconi, Maria Grazia
Abstract: Selective hydrogenation (semi‐hydrogenation) reactions of alkynes rely on Pd‐based catalysts to provide the correct pathway to favour formation of double bonds and avoid full hydrogenation to single bonds. Here, we present the preparation and characterisation of "Pd3 In"/TiO2 nanocatalysts, which show improved activity and selectivity compared to pure Pd catalysts, towards the liquid phase semi‐hydrogenation of 2‐methyl‐3‐butyn‐2‐ol (MBY) to 2‐methyl‐3‐buten‐2‐ol (MBE), a fundamental step in the preparation of pharmaceuticals, and other industrially produced substances, as well as a model reaction for the semi‐hydrogenation of alkynes. For both the supported and unsupported "Pd3 In" alloys (later re‐defined as Pd3−x In1+x ), we stabilised two new cubic polymorphs with a Pd‐like structure, instead of the tetragonal structure as reported so far in the literature. The stabilisation of these new polymorphs was made possible by using a solution‐based synthesis and, thanks to the use of different solvents, the reaction was carried out at different temperatures and the Pd/In ratio could be tuned. The same synthetic approach was adapted to prepare two "Pd3 In"/TiO2 catalysts by adding the TiO2 support to the reaction mixture, in a practical one‐step, one‐pot reaction. HREM and X‐Ray maps show that the cubic crystal structure of "Pd3 In" is maintained when prepared in the presence of the support, however, the support seems to influence the Pd/In ratio. Abstract : One step beyond the nano : New "Pd3 In"/TiO2 nanocatalysts show improved performance towards the liquid phase semi‐hydrogenation of 2‐methyl‐3‐butyn‐2‐ol (MBY). The catalysts are prepared via a one‐step one‐pot synthetic method and are based on two new cubic polymorphs of "Pd3 In", with tunable Pd/In ratios, thanks to the use of different solvents/temperatures during the synthesis process. PXRD, HREM and X‐Ray maps show that the cubic polymorphs are formed with or without the support, however, the support seems to influence the Pd/In ratio.